WITHDRAWN-Administrative Duplicate Publication: Complementary Therapies as a Strategy to Reduce Stress and Stimulate the Immunity of Women With Breast Cancer - Camila Aparecida Abrahão BScN, MD; Emiliana Bomfim BScN, MSc, PhD; Luís Carlos Lopes-Júnior BScN, OCN, MSc, PhD; Gabriela Pereira- (SAGE Publishing, 2019)
Abrahão, CA, Bomfim E, Lopes-Júnior LC, Pereira-da-Silva, G. Complementary Therapies as a Strategy to Reduce Stress and Stimulate the Immunity of Women With Breast Cancer. Journal of Evidence-Based Integrative Medicine. 2019; 24. Due to an administrative error, this article was accidentally published twice in Volume 24 with different DOIs. The correct and citable version of the article remains: Abrahão, CA, Bomfim E, Lopes-Júnior LC, Pereira-da-Silva, G. Complementary Therapies as a Strategy to Reduce Stress and Stimulate Immunity of Women With Breast Cancer. Journal of Evidence-Based Integrative Medicine . 2019; 24. doi: 10.1177/2515690X19834169